Multiplexed bacteriocin synthesis to combat and prevent antimicrobial resistance - Alex Quintero-Yanes; Kenny Petit; Hector Rodriguez-Villalobos; Hanne Vande Capelle; Olivier De Veirman; Hans Gerstmans; Joleen Masschelein; Juan Borrero; Pascal Hols; Philippe Gabant (Communications Biology)
Abstract Bacteriocins are underexplored yet promising candidates to combat antimicrobial resistance (AMR) and enable targeted therapy due to their natural origin, abundance and narrow spectrum of activity. In this study, we used a collection of engineered DNA devices and cell-free gene expression (CFE) to rapidly produce combinations (cocktails) of bacteriocins comprising both linear and circular proteins. Other cocktails were designed to target a specific bacterial species by leveraging insights into bacteriocin pathways for cell envelope penetration. These tailored combinations eradicated bacteria effectively while preventing resistance development. The synthesis of bacteriocins was optimized by using continuous exchange CFE, reengineering DNA parts, and adjusting conditions for disulfide bond formation. Also, we illustrate the efficacy of these bacteriocin mixtures against various multidrug-resistant human pathogens and highlight their potential through in vivo testing in the animal model Galleria mellonella. Our bacteriocin cocktail expression and test platform underscores the potential of bacteriocins for innovative treatments against multidrug-resistant infections.